2015
DOI: 10.3892/ijo.2015.2855
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chromosomal rearrangements involving non-ETS genes in prostate cancer

Abstract: Prostate cancer is characterized by structural rearrangements, most frequently including translocations between androgen-dependent genes and members of the ETS family of transcription factor like TMPRSS2:ERG. In a recent whole genome sequencing study we identified 140 gene fusions that were unrelated to ETS genes in 11 prostate cancers. The aim of the present study was to estimate the prevalence of non-ETS gene fusions. We randomly selected 27 of these rearrangements and analyzed them by fluorescence in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…THSD7B , a gene involved in the TGFβ signaling pathway, has been previously found to be the target for mutations [ 45 ]. NCKAP5 is a gene in the large region of inversion at 2q21.3-q22.1 and has been observed to be rearranged in prostate cancer by FISH [ 46 ]. Regions of inversions were also observed in GISTIC detected deletions ( S15 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…THSD7B , a gene involved in the TGFβ signaling pathway, has been previously found to be the target for mutations [ 45 ]. NCKAP5 is a gene in the large region of inversion at 2q21.3-q22.1 and has been observed to be rearranged in prostate cancer by FISH [ 46 ]. Regions of inversions were also observed in GISTIC detected deletions ( S15 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…20 Another study found reduced nuclear ZHX2 protein levels in HCC compared with surrounding non-tumor tissue, demonstrating that ZHX2 might also be regulated posttranscriptionally. [22][23][24] Chromosomal rearrangement at t(4;8)(q27;q24) that include the ZHX2 gene are associated with decreased ZHX2 expression in Hodgkin lymphoma. 21 Polymorphisms in the ZHX2 gene and disregulated ZHX2 expression have been reported in other cancers, including multiple myeloma, thyroid carcinoma and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…21 Polymorphisms in the ZHX2 gene and disregulated ZHX2 expression have been reported in other cancers, including multiple myeloma, thyroid carcinoma and prostate cancer. [22][23][24] Chromosomal rearrangement at t(4;8)(q27;q24) that include the ZHX2 gene are associated with decreased ZHX2 expression in Hodgkin lymphoma. 25 Since HBV is one of the common risk factors for HCC, we hypothesized that HBV might also influence ZHX2 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Some genes such as PTPRD, LRP1B and LINGO2 , which are target for homozygous deletions in HNSCC cell lines, showed frequent hemizygous deletions in the PPOL cell lines suggesting further selection in progression to HNSCC. Deletion of NCKAP5 was explored a little further (S7) as rare SCNAs involving NCKAP5 have been reported recently in HNSCC (3) (in supplementary data) and in prostate cancer (27). Potentially deleterious mutations have been reported in COSMIC (S7 Table).…”
Section: Resultsmentioning
confidence: 99%